On the sensitivity of atmospheric Cherenkov telescope arrays for regions with presence of multiple gamma-ray sources. Issue 5 (May 2016) - Ambrogi, L; Aharonian, F; De Oña Wilhelmi, E
Abstract: The potential of a next-generation ground based gamma-ray telescope array has been investigated. In addition to the ideal Gaussian shaped PSF, more realistic non-Gaussian PSFs with tails have been considered and their impact on the detector performance has been studied. The capability of the instrument to resolve multiple sources has been analyzed and the corresponding detector sensitivity estimated. These scenarios are particularly interesting in the framework of Galactic objects, where the observation of more than one source in the same field of view (FoV) is very likely to happen.